Information consultants in action, editado por J. Stephen Parker - Tarapanoff, Kira (Revista de Biblioteconomia de Brasília, 1987)
PARKER, J. Stephen (ed.) Information consultants in action. London; NewYork: Mansell Publishing Ltd. (a subsidiary of the H. W. Wilson Co.)., 1986. 258p. (Information Adviser series). ISBN0-7201-1753-4.